Analisis Faktor Risiko Pasien Penyakit Ginjal Kronik yang Menjalani Hemodialisis - Nur, Mohamad; Khalilah, Nur; Denta, Anggeria Oktavisa; Mumpuningtias, Elyk Dwi (Fakultas Ilmu Kesehatan, 2025)
Chronic Kidney Disease (CKD) is a global health problem with increasing number of cases and morbidity rates. This study aims to analyze the risk factors associated with CKD in patients receiving hemodialysis therapy. The study design used a case-control study approach with 30 respondents selected purposively, consisting of 15 CKD patients as the case group and 15 hypertensive patients without CKD as controls. Inclusion criteria for the case group included patients aged 30–65 years who had been diagnosed with end-stage CKD and underwent regular hemodialysis, while the control group consisted of hypertensive patients without impaired kidney function with the same age. All respondents must be willing to participate in the study and sign an informed consent. The exclusion criteria for both groups included patients with a history of autoimmune disease, diabetes mellitus, other chronic diseases that affect kidney function, long-term use of nephrotoxic drugs, and the inability to fully participate in the research process. The research data were analyzed using the chi-square test to determine the relationship between hypertension, diet, and the risk of CKD. Statistical tests showed that a history of hypertension increased the risk of CKD with a p value of 0.003, unhealthy diet was associated with CKD with a p value of <0.05, and the relationship between hypertension and CKD risk with a ϕ value of 0.533. The results of this study indicate that hypertension and unhealthy diet play a significant role in the development of CKD, providing important guidance for health intervention programs. Hypertension and unhealthy diet are major risk factors for CKD in hemodialysis patients.